2016
DOI: 10.1051/0004-6361/201527229
|View full text |Cite
|
Sign up to set email alerts
|

High resolution observations with Artemis-IV and the NRH

Abstract: Context. Narrow-band bursts appear on dynamic spectra from microwave to decametric frequencies as fine structures with very small duration and bandwidth. They are believed to be manifestations of small scale energy release through magnetic reconnection. Aims. We analyzed 27 metric type IV events with embedded narrow-band bursts, which were observed by the ARTEMIS-IV radio spectrograph from 30 June 1999 to 1 August 2010. We examined the morphological characteristics of isolated narrow-band structures (mostly sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 40 publications
3
38
0
7
Order By: Relevance
“…In Table 1 we summarize the average parameters of the type IIassociated spike-like structures. These parameters are very close to the corresponding parameters of type IV-associated spikes from Bouratzis et al (2016, their Table 1), which are also included in the table for comparison.…”
Section: Fine Structuresupporting
confidence: 67%
See 2 more Smart Citations
“…In Table 1 we summarize the average parameters of the type IIassociated spike-like structures. These parameters are very close to the corresponding parameters of type IV-associated spikes from Bouratzis et al (2016, their Table 1), which are also included in the table for comparison.…”
Section: Fine Structuresupporting
confidence: 67%
“…Type_II_FS_Revision02corr Table 1. Parameters of type II-associated spike-like bursts and type IV-associated spikes from Bouratzis et al (2016 the differential spectrum. They are nearly vertical in the dynamic spectrum, hence they look more like pulsations rather than herringbones.…”
Section: Fine Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have ulilized the polarimetric imaging capabilities of the NRH to examine spatial variation in radio bursts. For example, Mercier (1990) showed that Type III bursts have different spatial characteristics in circular polarization compared to the total intensity, and Bouratzis et al (2016) investigated similar differences in spike bursts as a function of time. Several others have examined source positions and structures in total intensity NRH observations, while using the polarization information to help discriminate between emission mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…From the original NRH visibilities, we computed 2D images with a resolution of 1.04 by 1.52 at 432 MHz. In a previous work on spike bursts (Bouratzis et al 2016) we also computed 1D images using visibilities from the east-west (EW) and northsouth (NS) arrays only; this improved the resolution by a factor of two, due to the fact that the extension antennas make a very small contribution to the 2D images. In the present case these 1D images were relatively noisy, whereas the fiber sources were well resolved and thus we preferred to compute 1D images by integrating the 2D images along the EW and NS directions.…”
Section: Observations and Their Analysismentioning
confidence: 99%